In vitro Anticancer Activity of the Polar Fraction From the Lophocereus schottii Ethanolic Extract - Orozco-Barocio, Arturo; Robles-Rodríguez, Blanca Susana; Camacho-Corona, María del Rayo; Méndez-López, Luis Fernando; Godínez-Rubí, Marisol; Peregrina-Sandoval, Jorge; Rivera, Gildardo; Rojas Mayorquín, Argelia E.; Ortuno-Sahagun, Daniel (Frontiers in Pharmacology, 2022)
Cancer is an increasingly common disease and is considered one of the main causes of death in the world. Lophocereus schottii (L. schottii) is a cactus used in Mexico in traditional medicine for cancer treatment. This study aimed to determine the effect of the ethanolic extract and the polar and nonpolar fractions of L. schottii in murine L5178Y lymphoma cells in vitro, analyzing their effect on the proliferative activity of splenocytes and to establish the effective concentration 50 (EC50) of the polar fraction. In addition, the secondary metabolites present in the extracts were determined by Ultra-Performance Liquid Chromatography-Mass Spectrometry (UPLC-MS). The study establishes that the three extracts of L. schottii have a cytotoxic effect on L5178Y cells and on the splenocytes stimulated with ConA. Additionally, the polar fraction has a significantly greater effects being three times more effective than cyclophosphamide on inhibiting the viability of L5178Y cells. Secondary metabolites present are mainly flavonoids and alkaloids, but there are also some terpenoids and sterols. Ultimately, polar fraction can be considered an anticancer substance, since its EC50 of 15 µg/mL is within the parameters established by the National Cancer Institute (NCI).